Recycling spent Pleurotus eryngii substrate supplemented with Tenebrio molitor feces for cultivation of Agrocybe chaxingu - Xian-lu Zeng; Fei Han; Jing-li Ye; Yan-mei Zhong (International Journal of Recycling of Organic Waste in Agriculture)
Abstract Purpose In the industrialized production of mushrooms usually only one flush of fruitbody is harvested, so that nutrients and energy in the substrate is not fully exploited. In this study, the spent Pleurotus eryngii substrate was recycled for the cultivation of Agrocybe chaxingu under ambient temperature. Method Six formulae were tested: (1) Control: 98% spent substrate, 1% sucrose, 1% lime; (2) Control + 10% wheat bran; (3) Control + 20% wheat bran; (4) Control + 10% T. molitor feces; (5) Control + 20% T. molitor feces; (6) Control + 10% wheat bran + 10% T. molitor feces. Results Two flushes of fruitbody were harvested, the control substrate resulted in a biological efficiency of 40.42%; the formulae with supplementation of 10% wheat bran, 20% wheat bran and 10% T. molitor feces significantly increased biological efficiency to 52.50, 54.61 and 51.56%, respectively, and supplementation of 20% T. molitor feces, or 10% wheat bran plus 10% feces further significantly increased biological efficiency to 62.95 and 61.10%, respectively. All supplemented substrates had significantly higher cellulose and laccase activity than the Control (cellulase 0.10 U/g; laccase 41.00 U/g), which were 10% wheat bran (0.15 U/g; 72.67 U/g), 10% T. molitor feces (0.17 U/g; 98.33 U/g), 20% wheat bran (0.22 U/g; 76.00 U/g), 20% T. molitor feces (0.27 U/g; 87.00 U/g), 10% wheat bran plus 10% T. molitor feces (0.25 U/g; 97.67 U/g), respectively. Conclusion Spent Pleurotus eryngii substrate was promising for cultivation of Agrocybe chaxingu, especially when supplemented with 20% T. molitor feces, or with 10% T. molitor feces plus 10% wheat bran.